Transformasi Informasi pada Literasi Digital di Desa Dengan ISO 29995:2021 - Pongtambing, Yulita Sirinti; Pitrianti, Siti; Novitasari, Ani; Sampetoding, Eliyah A M (Puslitbang Sinergis Asa Professional, 2024)
The development of technology and information has changed how people communicate today, leading to the digital concept. The use of digital concepts must begin with an assessment of digital literacy through valid measuring tools. This research aims to make ISO 29995:2021 the basis for making valid measuring instruments for digital literacy, especially in the village context. The research method in this study used PRISMA (Preferred Reporting Items for Systematic Review and Meta-analyses) by screening 988 articles based on inclusion and exclusion criteria, resulting in 8 articles that were further analyzed. The results show no valid digital literacy instrument was used in the village context. ISO 29995:2021 can be recommended as one of the cornerstones in creating valid instruments.